2014
DOI: 10.1016/j.exphem.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

mRNA regulation of cardiac iron transporters and ferritin subunits in a mouse model of iron overload

Abstract: Iron cardiomyopathy is the leading cause of death in iron overload. Men have twice the mortality rate of women, though the cause is unknown. In hemojuvelin-knockout mice, a model of the disease, males load more cardiac iron than females. We postulated that sex differences in cardiac iron import cause differences in cardiac iron concentration. RT-PCR was used to measure mRNA of cardiac iron transporters in hemojuvelin-knockout mice. No sex differences were discovered among putative importers of non-transferrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
12
1
1
Order By: Relevance
“…Plasma ALT activity, plasma NTBI concentrations and liver iron accumulation in the BKO-N diet mice were not much different from those in the WT-N diet mice, whereas levels of these parameters were considerably increased in the BKO-Fe diet mice. Some other groups have demonstrated that mRNA expressions of iron-regulatory proteins such as hepcidin, ferroportin, and transferrin receptors vary between the genders of the mice [37,38]. However, we did not find any difference in hepatic Hamp1 mRNA expression between male and female of WT and BKO mice in this study.…”
Section: Discussioncontrasting
confidence: 91%
“…Plasma ALT activity, plasma NTBI concentrations and liver iron accumulation in the BKO-N diet mice were not much different from those in the WT-N diet mice, whereas levels of these parameters were considerably increased in the BKO-Fe diet mice. Some other groups have demonstrated that mRNA expressions of iron-regulatory proteins such as hepcidin, ferroportin, and transferrin receptors vary between the genders of the mice [37,38]. However, we did not find any difference in hepatic Hamp1 mRNA expression between male and female of WT and BKO mice in this study.…”
Section: Discussioncontrasting
confidence: 91%
“…Additional literature also suggests that the link between ferritin, hepcidin, and dysmetabolic features may be particularly relevant in women . The role of sex hormones in the regulation of ferritin and hepcidin expression may also be responsible to a certain extent for the sex‐related differences observed in the present study and has recently been studied in animal models . Yet, although we adjusted for menopausal status and other established CV/metabolic risk factors, levels of ferritin remained associated with incident HF in women.…”
Section: Discussionmentioning
confidence: 61%
“…The biology of serum ferritin is poorly understood. Ferritin is primarily an intracellular protein produced to protect cells from labile intracellular iron (Brewer et al, 2014). Most of the circulating Patients were undergoing routine clinical assessment of cardiac T2* and LIC at 1-to 2-year intervals.…”
Section: Serum Ferritinmentioning
confidence: 99%